Heterogeneous resistance mechanisms in an EGFR exon 19-mutated non-small cell lung cancer patient treated with erlotinib: Persistent FGFR3-mutation, localized transformation to EGFR-mutated SCLC, and acquired T790M EGFR-mutation. (November 2017) - Santoni-Rugiu, Eric; Grauslund, Morten; Melchior, Linea C.; Costa, Junia C.; Sørensen, Jens B.; Urbanska, Edyta M.
Highlights: Heterogeneous mechanisms of TKI-resistance in EGFR -mutated NSCLC are described. Concomitant unreported FGFR3 -mutation occurring before and during TKI-treatment. Transformation to EGFR -mutated SCLC at first progression during TKI-therapy. Recurrence of NSCLC phenotype with acquired T790M EGFR -mutation at second progression. Genetic and phenotypic variation of TKI-resistant cells occurs during time in NSCLC. Abstract: Patients with epidermal growth factor receptor ( EGFR ) gene-mutated non-small cell lung cancer (NSCLC) obtain substantial clinical benefit from EGFR tyrosine-kinase inhibitors (TKIs), but will ultimately develop TKI-resistance resulting in median progression-free survival of 9–15 months during first-line TKI-therapy. However, type and timing of TKI-resistance cannot be predicted and several mechanisms may simultaneously/subsequently occur during TKI-treatment. In this respect, we present a 49 year-old Caucasian male ex-smoker with metastatic pulmonary adenocarcinoma (ADC) that concomitantly harbored an EGFR exon 19-mutation (p.E746_A750delELREA) and a previously unreported 2 bp frame-shift microdeletion in the fibroblast growth factor receptor 3 ( FGFR3 ; p.D785fs*31) gene. Interestingly, FGFR3 -mutations have previously been described in other cancer types of Caucasian patients and may represent an alternative pathway to EGFR-signaling. The patient received first-line erlotinib but after only 7 weeks showed metastatic pleural effusion, in which transformation to small cell lung cancer (SCLC) that retained the EGFR - and FGFR3 -mutations was identified. Consequently, standard carboplatin-etoposide regimen for SCLC combined with erlotinib continuation was implemented obtaining significant objective response. However, after completing 6 cycles of this combination, new pulmonary and hepatic metastases appeared and showed persistence of the original EGFR - and FGFR3 -mutated ADC phenotype together with acquisition of the erlotinib-resistant T790M EGFR -mutation. The patient rapidly deteriorated and deceased. Thus, this advanced EGFR -mutated NSCLC displayed very rapid onset and heterogeneous genetic and phenotypic mechanisms of TKI-resistance occurring at different times and locations of metastatic disease: concomitant FGFR3 -mutation before and during TKI-treatment as potential intrinsic mechanism for the rapid progression; transformation to SCLC at first progression during TKI-therapy; acquired T790M EGFR -mutation at second progression. Our case also underlines that, when achievable, rebiopsies of progressive sites during TKI-treatment are important for identifying heterogeneous histopathological and molecular resistance mechanisms and better defining possible treatment modifications.